Annealing kinetics of radiation damage in zircon. (15th March 2019) - Ginster, Ursula; Reiners, Peter W.; Nasdala, Lutz; Chanmuang N., Chutimun
Abstract: Models of noble-gas diffusion in minerals are essential for thermochronologic interpretations used for understanding the timing and rates of a range of geologic processes including exhumation and burial. For some minerals, diffusive daughter loss depends not only on temperature but also radiation damage. This is particularly true for the zircon (U-Th)/He system. Consequently, realistic interpretation of zircon (U-Th)/He thermochronology needs to account for both accumulation as well as annealing of radiation damage as a function of time and temperature. To date, models use etchable fission track annealing as a proxy for bulk radiation damage annealing. Here we present experimental annealing data and models of bulk radiation damage annealing kinetics in zircon. We show that bulk radiation damage annealing requires significantly higher temperatures and longer durations than that of etchable fission tracks. When fission tracks are completely annealed, bulk radiation damage has been annealed by only 30–50%. Consequently, a zircon (U-Th)/He thermochronology model that uses a fission track annealing algorithm will overestimate annealing resulting in erroneous estimates of He diffusivities and He loss. A time-temperature (t-T) history derived using the fission track annealing algorithm can, therefore, differ significantly from a t-T path derived using bulk radiation damage annealing kinetics. We also show that fractional-annealing-progress depends on the extent of accumulated radiation damage. Accordingly, we present distinct annealing models for low-, moderate-, and high-damage zircon. Each model comprises three annealing regimes with distinct kinetic parameters. The low-fractional annealing (low-φ) regime applies at low temperatures and short heating durations, whereas the high-φ regime applies at high temperatures and long durations. Between the two is a transition regime. We attribute the change in annealing kinetics to the presence of multiple damage-induced defect types that anneal with different activation energies and, therefore, at distinct time-temperature conditions. Comparison with other studies suggest that the low-φ regime is dominated by annealing of point defects that anneal at low temperatures, whereas the high-φ regime is dominated by epitaxial growth and annealing of isolated, stable point defects that anneal with high activation energies.